Пошаговое объяснение:
(х + 7,2) - 4 1/2 = 6 9/20
(Х+7,2)-4 1/2=6 9/20
Х+7,2-4,5=6 9/20
Х+2,7=6 9/20
Х=6 9/20-2,7
Х=6 9/20-2 7/10
Х=6 9/20-2 14/20
Х=3 15/20
Проверка
3 15/20+7,2-4 1/2=6 9/20
3 15/20+7 1/5-4 1/2=6 9/20
Общий знаменатель 20
3 15/20+7 4/20-4 10/20=6 9/20
10 19/20-4 10/20=6 9/20
6 9/20=6 9/20
Пошаговое объяснение:
(х + 7,2) - 4 1/2 = 6 9/20
(Х+7,2)-4 1/2=6 9/20
Х+7,2-4,5=6 9/20
Х+2,7=6 9/20
Х=6 9/20-2,7
Х=6 9/20-2 7/10
Х=6 9/20-2 14/20
Х=3 15/20
Проверка
3 15/20+7,2-4 1/2=6 9/20
3 15/20+7 1/5-4 1/2=6 9/20
Общий знаменатель 20
3 15/20+7 4/20-4 10/20=6 9/20
10 19/20-4 10/20=6 9/20
6 9/20=6 9/20
Пошаговое объяснение: